2016
DOI: 10.1016/j.scitotenv.2015.08.137
|View full text |Cite
|
Sign up to set email alerts
|

Levels and profiles of brominated and chlorinated contaminants in human breast milk from Thessaloniki, Greece

Abstract: Human breast milk samples (n=87) collected between July 2004 and July 2005 from primipara and multipara mothers from Thessaloniki, Greece were analysed for six groups of persistent organic pollutants (POPs): polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane and its metabolites (DDTs), chlordane compounds (CHLs), hexachlorocyclohexane isomers (HCHs) and hexachlorobenzene (HCB). DDTs [median: 410ng/g lipid weight (lw)], PCBs (median: 90ng/g lw) and HCHs (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…In some regions of China, the DDTs concentration in soils still exceed soil quality standards due to previous accumulation and slow degradation (Feng et al, 2003;Shi et al, 2005;Zhong et al, 2011). DDTs also continue to accumulate in the food chain and has been found in human adipose and breast milk (Dimitriadou et al, 2016). Other man-made organochlorine compounds, such as polychlorinated biphenyls (PCBs) and pentachloronitrobenzene (PCNB), also persist in soils and have become serious environmental problems (Hu et al, 2008;Li and Yang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In some regions of China, the DDTs concentration in soils still exceed soil quality standards due to previous accumulation and slow degradation (Feng et al, 2003;Shi et al, 2005;Zhong et al, 2011). DDTs also continue to accumulate in the food chain and has been found in human adipose and breast milk (Dimitriadou et al, 2016). Other man-made organochlorine compounds, such as polychlorinated biphenyls (PCBs) and pentachloronitrobenzene (PCNB), also persist in soils and have become serious environmental problems (Hu et al, 2008;Li and Yang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In another study in China, egg consumption was suggested to be a pathway for exposure to BDEs (Zheng et al 2015). One or more BDEs have been detected in breast milk (Chao et al 2010;Dimitriadou et al 2016;Kim et al 2012). reported to be the prevailing congener in waste water sludge, along with 47,49,66,85,99,100,153,154, and 183 which were detected in lower concentrations (Stiborova et al 2015).…”
Section: Sources Of Exposure To Polybrominated Diphenyl Ethers and Gementioning
confidence: 97%
“…The levels of PBDEs and PCBs were measured using GC-MS method in the human milk samples (n = 87) collected between July 2004 and July 2005 from primipara (n = 34) and multipara (n = 53) mothers from Thessaloniki, Greece [62]. The median values of PBDEs and PCBs were determined 1.5 ng/g lw and 90 ng/g lw, respectively.…”
Section: Lc-ms/ms and Gc-msmentioning
confidence: 99%